“SAMBAT” SEBAGAI UPAYA MENGATASI SELF HEALING (KAJIAN AL QUR’AN SURAT RAD AYAT 28) - Laila Nadzifatus Syarifah (Yayasan Literasi Sains Indonesia, 2023)
There is Someone who experience emotional wounds and they have problems with their psychology, then the term self-healing becomes something that is familiar to us. This self-healing becomes a process of restoring one’s self-condition. A person who experiences mental wounds cannot be healed on their own because when someone experiences this, the negative impact ends up being the impact. Actually, the forms of self-healing that can be done are very varied, one of which is the term